Non‐allergic rhinitis: Position paper of the European Academy of Allergy and Clinical Immunology. Issue 11 (2nd June 2017) - Hellings, P. W.; Klimek, L.; Cingi, C.; Agache, I.; Akdis, C.; Bachert, C.; Bousquet, J.; Demoly, P.; Gevaert, P.; Hox, V.; Hupin, C.; Kalogjera, L.; et al.
Abstract: This EAACI position paper aims at providing a state‐of‐the‐art overview on nonallergic rhinitis (NAR). A significant number of patients suffering from persistent rhinitis are defined as nonallergic noninfectious rhinitis (NANIR) patients, often denominated in short as having NAR. NAR is defined as a symptomatic inflammation of the nasal mucosa with the presence of a minimum of two nasal symptoms such as nasal obstruction, rhinorrhea, sneezing, and/or itchy nose, without clinical evidence of endonasal infection and without systemic signs of sensitization to inhalant allergens. Symptoms of NAR may have a wide range of severity and be either continuously present and/or induced by exposure to unspecific triggers, also called nasal hyperresponsiveness (NHR). NHR represents a clinical feature of both AR and NAR patients. NAR involves different subgroups: drug‐induced rhinitis, (nonallergic) occupational rhinitis, hormonal rhinitis (including pregnancy rhinitis), gustatory rhinitis, senile rhinitis, and idiopathic rhinitis (IR). NAR should be distinguished from those rhinitis patients with an allergic reaction confined to the nasal mucosa, also called "entopy" or local allergic rhinitis (LAR). We here provide an overview of the current consensus on phenotypes of NAR, recommendations for diagnosis, a treatment algorithm, and defining the unmet needs in this neglected area of research.